2015
DOI: 10.1007/s11192-015-1768-2
|View full text |Cite
|
Sign up to set email alerts
|

Participations to European Framework Programs of higher education institutions and their association with organizational characteristics

Abstract: This paper aims to analyze patterns of participation of higher education institutions (HEIs) to European Framework Programs (EU-FP) and their association with HEI characteristics, country and geographical effects. We have analyzed a sample of 2235 HEIs in 30 countries in Europe, derived from the European Tertiary Education Register (ETER), which has been matched with data on participations in EU-FPs in 2011 using the EUPRO database. Our findings identified (1) a high concentration of EU-FP participation in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 52 publications
2
42
0
Order By: Relevance
“…The few studies dealing with this level of analysis have indicated skewed distribution of participation, without concluding as to whether allocation of funding is non-meritocratic (5,16,43,44). Large and highly reputed HEIs are generally most successful in applying for funding in EU FP projects (45).…”
Section: Organizational Resources and Capabilitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The few studies dealing with this level of analysis have indicated skewed distribution of participation, without concluding as to whether allocation of funding is non-meritocratic (5,16,43,44). Large and highly reputed HEIs are generally most successful in applying for funding in EU FP projects (45).…”
Section: Organizational Resources and Capabilitiesmentioning
confidence: 99%
“…Our empirical analysis is based on the European Tertiary Education Register (ETER) database 1 (47). The data contain detailed organizational-level statistics on research and education, and have been used previously for similar types of analyses (5). We extracted a as successful applications for H2020.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…This gap, in turn, has prompted research authorities in many European countries to a search for ways of increasing their countries' participation in the FPs and inspired many European researchers to explore why some countries are more successful than others at securing European research and innovation grants. The result of this effort is that there is now an extensive literature discussing factors that primarily enable universities to obtain funding from the FPs (Enger and Castellacci 2016;Lepori et al 2015;Neufeld, Huber, and Wegner 2013), less so on private firms.…”
Section: Introductionmentioning
confidence: 99%